2017
DOI: 10.1038/cr.2017.76
|View full text |Cite
|
Sign up to set email alerts
|

Homology-mediated end joining-based targeted integration using CRISPR/Cas9

Abstract: Targeted integration of transgenes can be achieved by strategies based on homologous recombination (HR), microhomology-mediated end joining (MMEJ) or non-homologous end joining (NHEJ). The more generally used HR is inefficient for achieving gene integration in animal embryos and tissues, because it occurs only during cell division, although MMEJ and NHEJ can elevate the efficiency in some systems. Here we devise a homology-mediated end joining (HMEJ)-based strategy, using CRISPR/Cas9-mediated cleavage of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
315
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(330 citation statements)
references
References 30 publications
(59 reference statements)
11
315
2
2
Order By: Relevance
“…The researchers showcased homology‐mediated gene integration utility by designing the new homology‐mediated end joining (HMEJ) donor sequence that requires sgRNA target sites as well as ~800 bp homology arms. The HMEJ‐based strategy yielded a high penetrance gene transmission than existing strategies in multiple systems . More importantly, this approach achieved gene‐edited monkeys by coinjection of different volumes and concentrations of donor plasmid together with Cas9 mRNA .…”
Section: Crispr‐cas9—lots Of Choices For Gene Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers showcased homology‐mediated gene integration utility by designing the new homology‐mediated end joining (HMEJ) donor sequence that requires sgRNA target sites as well as ~800 bp homology arms. The HMEJ‐based strategy yielded a high penetrance gene transmission than existing strategies in multiple systems . More importantly, this approach achieved gene‐edited monkeys by coinjection of different volumes and concentrations of donor plasmid together with Cas9 mRNA .…”
Section: Crispr‐cas9—lots Of Choices For Gene Targetingmentioning
confidence: 99%
“…The efficiency of targeted transgenes knock-in illustrated by recent reports, further highlighting the broad promise of CRISPR-Cas9-mediated PITCh (CRIS-PITCh) systems via microhomology-mediated end joining (MMEJ). 15,19,24,25 This method utilities original CRIS-PITCh vector (v1) and upgraded PITCh version (CRIS-PITCh (v2)) for external DNA knock-in ( Figure 1A,B). For a practical application, CRIS-PITCh-v2 system was applied to transfer anti-prion scFv-Fc antibody into the hypoxanthine phosphoribosyltransferase (hprt) locus of CHO cell lines.…”
mentioning
confidence: 99%
“…Interestingly, the efficiency of insertion of 714 bp in human cells was the same regardless if the homology arms were 33 bases or 518 bases [Paix et al 2017a]. This is in contrast to the HMEJ experiments described above [Yao et al 2017] where long homology arms perform better than short homology arms. A detailed protocol on performing edits of either DNA insertions or deletions using short homology arms has recently been published and contains useful tips [Paix et al 2017b].…”
Section: Recent Advances For Site-specific Insertion Of Relatively Lamentioning
confidence: 99%
“…Inspired by this, we generated site‐specific Uncoupling protein 1 ( UCP1 ) knock‐in pigs efficiently and reconstituted UCP1 expression in porcine white adipose tissue via such HITI strategy (unpublished data). Recently, microhomology‐mediated end joining (MMEJ)‐ and homology‐mediated end joining (HMEJ)‐based strategies are reported to have the capable of integrating long exogenous DNA fragments into the genome at relatively high frequencies (Figure a) (Nakade et al, ; Yao et al, ), which suggested that these HDR dependent and independent strategies are most sensible to introduce site‐specific transgene integration without the cell cycle dependence and is free from the exogenous molecule cytotoxicity.…”
Section: Improved Understanding Of Crispr/cas Systemsmentioning
confidence: 99%